Reinterpretasi Ayat-ayat Perang Perspektif Fiqh Siyasah - Sulhadi, Asep; Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2024)
This article discusses the application of war verses in the Qur’an using the fiqh siyasah approach. The main issue addressed is how to apply and interpret the war verses through this approach. This research falls under the category of a literary study. The method employed by the author is a descriptive-analytical method using fiqh siyasah as the primary framework. This article is significant because, upon observing contemporary Muslim religious practices, there appears to be a tendency to understand Qur'anic verses in a textual and rigid manner. Through the fiqh siyasah approach, it is evident that war in Islam is only permissible when Muslims are harmed or expelled from their homeland, preventing them from fulfilling religious obligations as required. From the perspective of fiqh siyasah, war is not for offensive purposes but rather for defensive ones. Consequently, war must cease when the enemy no longer disturbs Muslims or incites discord.